Implementing a trauma‐informed system of care: An analysis of learning collaborative outcomes. Issue 2 (30th March 2023) - Bills, Lyndra J.; Hutchison, Shari L.; Snider, Mira D. H.; Skrzypek, Brittany E.; Minnich, Christopher L.; Korney, Joseph M.; Taylor, RaeAnn M.; Herschell, Amy D.
Abstract: Trauma exposure can negatively impact health. Trauma‐informed care implementation within health care systems may improve the identification and treatment of trauma‐related illness on a population health level. The current study investigated outcomes of a multiagency implementation of trauma‐informed care for Medicaid‐enrolled adults and children in 23 rural Pennsylvania (United States) counties. Changes in trauma symptom screening, the number of staff trained in trauma‐informed care, and clinician confidence in using trauma‐informed care were assessed in participating treatment agencies ( N = 22) over the course of a 15‐month trauma‐informed care learning collaborative (TLC). Data included monthly agency‐reported screening, training, and confidence outcomes, which were analyzed using repeated‐measures analyses of variance. Trauma symptom screening rates improved from 41.1% ( SD = 43.0%) to 93.3% ( SD = 12.0), p < .001; ηp 2 = .30. The average number of cumulative staff members trained in trauma‐informed care per agency increased from 24.43 ( SD = 42.22) to 140.00 ( SD = 150.87), p < .001, Kendall's W = .09. The percentage of agencies that reported high confidence in delivering trauma‐informed care increased from 15.8% ( SD = 15.5%) to 80.5% ( SD = 17.7%), p < .001; ηp 2 = .45. Pairwise comparisons revealed both screening rates and confidence ratings reached significant improvement in Month 11 of the TLC, suggesting that these processes may be related. A total of 2, 935 staff members were trained during the TLC. The immediate impact of system‐level implementation of trauma‐informed care was evident for agency processes and staff confidence, with support provided by multiple stakeholders.